Supplemental carbohydrate ingestion does not improve performance of high-intensity resistance exercise - Kulik, J. R.; Touchberry, C. D.; Kawamori, N.; Blumert, P. A.; Crum, A. J.; Haff, G. G. (The Journal of Strength and Conditioning Research, 2008)
The effects of supplemental carbohydrate (CHO) ingestion on the performance of squats to exhaustion (STE) were investigated with eight resistance-trained men. Subjects participated in a randomized, counterbalanced, double-blind, placebo-controlled protocol with testing separated by 7 days. Subjects consumed 0.3g.kgCHO/bodymass or a placebo (PLC) of equal volume immediately before exercise and after every other successful set of squats. The STE consisted of sets of five repetitions at an intensity of 85% 1 repetition maximum (1RM). Performance measured as total sets (CHO 3.5 +/- 3.2, PLC 3.5 +/- 2.7), repetitions (CHO 20.4 +/-14.9, PLC 19.7 +/- 13.1), volume load (CHO 2928.7 +/- 2219.5 kg, PLC 2772.8 +/- 1951.4 kg), and total work (CHO 29.9 +/- 22.3 kJ, PLC 28.6 +/- 19.5 kJ) was not statistically different between the CHO and PLC treatments. The results suggest that CHO supplementation does not enhance performance of squats performed with 85% 1RM to volitional failure.